MANAJEMEN PENINGKATAN MUTU PENDIDIKAN ISLAM - Fery Irianto Setyo Wibowo (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2023)
Management of Islamic Education is actually very helpful in efforts to improve the quality of educational institutions. Not only for Islamic educational institutions, but more than that, in addition to Islamic educational institutions, they can also study and apply Islamic education management. Not only madrasas have the right to apply Islamic education management, but public schools can also apply it to improve the quality of the school itself. Islamic education management that is applied in the operations of an educational institution (school) and used as a complement to the implementation of national education management will definitely support the achievement of improving the quality of educational institutions. Because it is indeed a complement and perfecter, if the management of Islamic education is applied in line with the management of national education, an increase in the quality of educational institutions can be immediately realized. The need for efforts to apply management of Islamic education in an educational institution (school) as an effort to improve the quality of educational institutions is not without reason. Precisely because the management of Islamic education is a complement and complement to the management of national education, it is necessary to implement management of Islamic education along with national education management.